2014
DOI: 10.5897/ijsa2014.0560
|View full text |Cite
|
Sign up to set email alerts
|

Gendered injustice: A comparative analysis of witchcraft beliefs and witchcraft-related violence in Ghana and Nepal

Abstract: Witch-hunt is an often overlooked but major social problem in many of the societies in the Global South. Ghana and Nepal represent two such societies where modern-day witch-hunt is frequently reported. This study examines the similarities and differences in witchcraft beliefs and practices in Ghana and Nepal as well as the perpetration of aggressive acts against putative witches in these two societies. Among the issues explored are superstition, witchcraft beliefs, socio-demographic characteristics of victims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Also, in a study with pregnant women in peri-urban Ghana, curses were perceived to be a possible cause of Hepatitis B [24]. These findings are not astounding because, in most Ghanaian societies, diseases with unusual presentations are attributed to evil influences [45–46]. We also identified that the belief PWHB attach to the aetiology of HBV seems to have an influence on the type of treatment they seek.…”
Section: Discussionmentioning
confidence: 81%
“…Also, in a study with pregnant women in peri-urban Ghana, curses were perceived to be a possible cause of Hepatitis B [24]. These findings are not astounding because, in most Ghanaian societies, diseases with unusual presentations are attributed to evil influences [45–46]. We also identified that the belief PWHB attach to the aetiology of HBV seems to have an influence on the type of treatment they seek.…”
Section: Discussionmentioning
confidence: 81%
“…This was due to its (perceived) inherent irrationality and for the political dangers it posed to colonial authority, having formed part of anti-colonial rebellions in places such as Tanzania ( Langwick, 2011 ). Anti-sorcery or anti-witchcraft ordinances were passed in many colonies, although the scope of what and who was liable to be criminalised differed somewhat depending on the jurisdiction in question ( Roberts, 1935 ; Mutungi, 1971 ; Niehaus, 2001 ; Mesaki, 2009 ). As indigenous knowledge and resources were appropriated by colonialists, local plants were dislocated from their broader healing networks and molecularised through the colonial scientific laboratory ( Merson, 2000 ; Osseo-Asare, 2014 ).…”
Section: Traditional Medicine and Its Politicsmentioning
confidence: 99%